APPLICATION OF COOPERATIVE LEARNING TYPE TWO STAY TWO STRAY (TSTS) LEARNING MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES IN HISTORY SUBJECTS AT SMK KANSAI PEKANBARU: Penerapan Media Kalender Cooperative Learning Type Two Stay Two Stray (TSTS) Untuk Meningkat Hasil Belajar Siswa Pada Mata Pelajaran Sejarah di SMK Kansai Pekanbaru - Mabrika Azzahra MZ; Isjon; Yanuar Al Fiqri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to improve student learning outcomes in History Learning for class XI TKR at SMK Kansai Pekanbaru through the application of the Cooperative Learning Type Two Stay Two Stray (TSTS) learning model. This study uses the Classroom Action Research (CAR) method which includes the stages of planning, implementation, observation and reflection. The research instrument includes the Teaching Module as a learning tool, observation sheets for teachers and students and tests as a data collection tool. This study was conducted in two cycles. Each cycle consists of two meetings. The results of the analysis showed that the increase in student learning outcomes in cycle I was 3 students (16.66%) achieving completion, while 15 students had not completed, so they had not met the target. In cycle II, the number of students who completed increased to 16 students (88.88%) with 2 students who had not completed. This achievement exceeded the classical completion target of 80%. These results indicate that the cooperative learning type Two Stay Two Stray (TSTS) model is effective in improving student learning outcomes in history subjects.